Influence of TiN inclusions and segregation bands on the mechanical properties and ballistic performance during ballistic impact tests in low-alloy high-strength steel - Tong, Keke; Sun, Haoran; Duan, Luxing; Zuo, Xiurong (Frontiers in Materials, 2025)
The influence of TiN inclusions and segregation bands on the mechanical properties and ballistic performance was investigated in high-strength steel. With ballistic test at a bullet impact velocity of about 810 m/s, the steel plate displayed the different ballistic performance, forming partially penetrated crater A and the completely penetrated crater B, despite the craters A and B were close together with only about 100 mm. The zone near crater A displayed excellent strength, plasticity and deformability than that near crater B. The segregation bands and TiN inclusions in steel plate originated from central segregation in continuous casting slabs. The Adiabatic shear bands (ASBs) with total length of 14,848 μm around crater B was more serious than that with total length of 6,239 μm around crater A, attributed to the low n value and strain hardening rate in completely penetrated crater region. Cracks parallel to the penetration direction only occurred around the crater B. Cracks also formed along the interfaces of ASB and matrix. The inhomogeneous deformation around ASBs resulted in stress concentration, especially at the interface between the matrix and the segregation band, making the long crack initiation and propagation under load of impact.